Religion and Media: Anthropological study of religious behavior in the film “Little House on the Prairie” - Tresnawaty, Betty; Risdayah, Enok (Department of Anthropology, Faculty of Social and Political Sciences, Hasanuddin University., 2023)
The purpose of this paper is to describe the real relationship between religion and media through the content of a film. On the other side, it opens up opportunities for the development of anthropology. Human culture as an object of anthropology, especially in remote areas or isolated ethnic groups, which was previously difficult to reach through the presence of high-tech media, is now beginning to be revealed. Film is a means of delivering messages to the public and is quite effective. One of these images is reflected in the film Little House on the Prairie. a television program that Televisi Republik Indonesia (TVRI) aired in the 1980s. Tells the story of a family living in a wooden house in a remote village with simple and basic living equipment. Meanwhile, it also reflects the religious behavior of a family that is obedient in carrying out religious orders. Literature study is the dominant data collection technique in this research and is a characteristic of the qualitative method. The results of this study found that the relationship between religion and the media can strengthen and develop other social sciences, especially social anthropology.